(untitled) (Педагогіка вищої та середньої школи, 2022)
Philosophi in metodological drowning of future teacher: role and structure of contecst. In the state we discribe duestions of philosophi in professional preparing of teacher as a metodological sight of this component. This part of philosophy can be strongering by efectsonal structure of philosophical study.